A CAST Analysis of an Accident of Software Project - Kusakabe Shigeru; Miwa Azuma (MATEC Web of Conferences, 2019)
We report a CAST analysis of a software project by a team across the primary and subcontractor companies focusing on a kind of safety, psychological safety. By using CAST, we can understand the context of the behaviours leading to the unintended event and avoid personal blames to keep psychological safety. The project was a software maintenance project, in which an online trading system went down in the production migration, the final phase before the system release. The end users had no damages in this case, but some members were going to lose respects from other members and stakeholders. The system down was caused by a defect, and the first investigation report simply blamed the subcontractor members related to the defect injection and leakage. The senior manager, who cares to build and maintain psychological safety in the team, wanted to conduct a deeper analysis to avoid personal blames. The CAST helped to uncover that process changes over time from the originally defined one contributed the injection and leakage of the defect. It turned out the process owner and manager at the primary contractor side had a part of the responsibility for the defect leakage. The senior manager made this conclusion shared among team members and succeeded to avoid losing psychological safety. We conclude the CAST based on STAMP is useful in analyzing issues of software project management such as psychological safety.